Case Report: A Case of Sarocladium strictum Meningoencephalitis in an Immunocompetent Patient After Invasive Operation - Cui, Yue; Meng, Jiali; Zhang, Jing; Wang, Lin; Yan, Haihan; Xia, Han; Cao, Jingrong; Wu, Liyong (Frontiers in Medicine, 2021)
As an opportunistic phytopathogen, Sarocladium strictum has only been shown to cause neurological disease in immunocompromised patients, where antifungal therapy was not effective. We report a case of Sarocladium strictum meningoencephalitis in an apparently immunocompetent young woman who presented with severe headache and slight fever after undergoing transnasal endoscopic repair of cerebrospinal fluid rhinorrhea. Chronic sinusitis and suspicious intracranial fungal lesions were observed on enhanced magnetic resonance imaging (MRI). Both culture and metagenomic next-generation sequencing of her cerebrospinal fluid were positive for Sarocladium strictum. After local debridement, treatment with amphotericin B plus voriconazole and Ommaya reservoir implantation, the patient improved significantly. Unfortunately, her symptoms worsened again despite plenty of antifungal therapy for a month.